1997
DOI: 10.1080/15575339709489780
|View full text |Cite
|
Sign up to set email alerts
|

Public Infrastructure in Economic Development and Growth: Evidence From Rural Manufacturers

Abstract: The role of public infrastructure in economic development and growth is examined and reported here. Specific attention is paid to the importance of infrastructure to small rural manufacturing firms in upper New England and Wisconsin. Study results suggest that while infrastructure is important to small manufacturing firms, other community attributes such as overall community attitudes toward change and the underlying forces of firm start-ups are more important. While adequate investments in infrastructure may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…Communities with higher levels of social capital have been found to do better economically (Putnam 2000). Halstead and Deller (1997) examined how community infrastructure impacts economic development in communities and found that it was quality of life that influenced individual companies more than physical infrastructure such as roads and bridges. Quality of life and social capital are often discussed in similar circles but the two are rarely examined together.…”
Section: Introductionmentioning
confidence: 99%
“…Communities with higher levels of social capital have been found to do better economically (Putnam 2000). Halstead and Deller (1997) examined how community infrastructure impacts economic development in communities and found that it was quality of life that influenced individual companies more than physical infrastructure such as roads and bridges. Quality of life and social capital are often discussed in similar circles but the two are rarely examined together.…”
Section: Introductionmentioning
confidence: 99%
“…Zekeri et al (1994) found that solidarity and past activism contribute to some types of community and economic development (recreation and tourism and human service development), but not to others (business and industry development). It is evident from this and other research (Halstead & Deller, 1997;Knaap & Simon, 1994) that features of social organization play a role in the choice and success of community economic development strategies. By extension, one would expect different features of social organization to facilitate one type of strategy versus another.…”
Section: Economic Development Strategiesmentioning
confidence: 65%
“…21 In contrast, Deller et al (2001) examine the effect of amenity and quality of life attributes on regional economic growth in the United States and find that predictable relationships exist between amenities, quality of life, and local economic performance. Likewise, Halstead and Deller (1997), Rudzitis (1999), andGottlieb (1994) find that quality of life plays an increasingly important role in community economic growth in the United States.…”
Section: Estimation Results Of the Employment Growth Modelmentioning
confidence: 99%